Understanding and evaluating shoulder pain in the throwing athlete - Garbis, N. G.; McFarland, E. G. (Physical Medicine & Rehabilitation Clinics of North America, 2014)
Shoulder pain in the throwing athlete can present at any age and in any level of sport and can lead to dysfunction. A thorough evaluation of the throwing athlete can often determine the cause of symptoms, which is frequently multifactorial. Although the pathophysiology leading to pain in the shoulder of the throwing athlete is not entirely known, nonoperative modalities remain the mainstay of treatment. In general, surgical intervention should be reserved as a last resort. Effective treatment often requires collaboration among trainers, players, physicians, and therapists to determine an appropriate course of action.